Assessment of filtration capacity of different bivalve species suitable for integrated multi-trophic aquaculture (IMTA) systems vis-à-vis waste valorization for sustainable environment - Maibam Malemngamba Meitei; Ande Penchala Muralidhar; Karthireddy Syamala; Srinivasan Sureesh; Gouranga Biswas; Sekar Megarajan; Sukham Munilkumar (Discover Sustainability)
Abstract Intensive aquaculture practices have increased waste production, including uneaten feed and bio-deposits, releasing nitrogen and phosphorus into the environment, often causing eutrophication. As filter feeders, bivalves can mitigate eutrophication through filtration and bioremediation. This study compared the filtration and bioremediation capacities of locally available bivalve species blood clam (Tegillarca granosa), oyster (Crassostrea madrasensis) and green mussel (Perna viridis) from the Kakinada coast, Andhra Pradesh, India, for their plankton-filtering capacity and potential for bioremediation of aquaculture wastewater. Laboratory experiments were conducted over five days in two settings: Microcosm (MI) experiment in 9 containers (5L) supplied with Thalassiosira sp. (2L) and Mesocosm (ME) experiment in 9 tanks (300L) supplied with 50L shrimp aquaculture wastewater. Bivalve density was set on 1 organism per 2L for MI and 2 individuals per 50L for ME. The experimental response variables were filtration rate (FR) and clearance rate (CR) of plankton and chlorophyll-a (Chl-a) for MI, and physico-chemical parameters and bacterial population for ME. No significant differences in the filtration and clearance rates of plankton and chlorophyll-a were observed among bivalve species. Plankton filtration efficiency of 94%, 87.1%, and 77.0% were observed in clams, oysters, and mussels, respectively, after five days. In the mesocosm experiment, there were no significant differences in the clearance rates of ammonia, nitrite, phosphate, BOD, and TDS among the species. However, oysters had significantly higher clearance rates of COD and TSS than blood clams and green mussels. The total bacterial count was significantly lower in the green mussel treatments than in oysters and clams. The results suggest that all bivalve species can reduce plankton and improve water physico-chemical parameters, making them suitable for integrated multi-trophic aquaculture (IMTA) systems. However, the economic importance, availability, and suitability of the species should be considered during selection.